Production of Surfactin from Bacillus subtilis ATCC 21332 by Using Treated Palm Oil Mill Effluent (POME) as Fermentation Media - Mohd Rizal Abas; Abdul Jalil Abdul Kader; Mohd Sahaid Khalil; Aidil Abdul Hamid; Mohd Hafez Mohd Isa (IACSITPress, Singapore, 2024)
Non-Indexed Publication